KELUARGA SAKINAH, MAWADDAH PERSPEKTIF HUKUM ISLAM - Samud Samudera; Wing Redy Prayuda (UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRAC Life in pairs is the nature of living things in the world. But only human beings are the only creatures of God capable of wrapping nature into a marriage bond. One of the goals of marriage is the formation of a harmonious family. In Islam a harmonious family is a family of sakinah, mawaddah, wa rahmah. Creating a sakinah family is not an easy thing. There needs to be an effort that leads to the process. Among other things, family members' awareness, socialization, guidance and encouragement to them to instill the values of the formation of family trust. There are still many households that are hit by conflicts or disputes which impact on the destruction of the family order from children to macro environments. The crisis in the household does not only occur among ordinary people but also occurs in the upper layers, including public figures or celebrities.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The results of this study are that families are expected to have professional abilities to anticipate the behavior of all family members consisting of various emotional and personality qualities, and family counseling can lead to habituation of daily behavior based on religious teachings to become a devoted, positive, productive and independent family through individual relations and family systems that are based on Islamic teachings and can realize the functions that exist in the family, so that the family avoids various problems. Keywords: Sakinah Family, Mawaddah, Rahmah and Islamic Law. ABSTRAKHidup berpasang-pasangan merupakan fitrah makhluk hidup di dunia. Namun hanya manusialah satu-satunya makhluk Allah yang mampu membungkus fitrah hidup dalam sebuah ikatan perkawinan. Salah satu tujuan perkawinan adalah terbentuknya keluarga yang harmonis. Dalam Islam keluarga harmonis adalah keluarga sakinah, mawaddah, wa rahmah. Mewujudkan sebuah keluarga sakinah memang bukanlah hal yang mudah. Perlu adanya upaya yang mengarah pada proses tersebut. Antara lain kesadaran anggota keluarga, sosialisasi, bimbingan dan dorongan kepada mereka untuk menanamkan nilai-nilai pembentukan keluarga sakinah. Masih banyak rumah tangga yang dilanda konflik atau pertengkaran sehingga berimbas pada rusaknya tatanan keluarga mulai dari anak sampai lingkungan yang bersifat makro. Krisis dalam rumah tangga bukan hanya terjadi dikalangan orang biasa melainkan juga banyak terjadi pada lapisan atas tidak terkecuali kalangan publik figur atau selebritis.Jenis penelitian ini adalah penelitian kepustakaan (library research), dalam artian semua sumber data berasal dari bahan-bahan tertulis berupa buku, dokumen, majallah dan naskah yang ada kaitannya dengan topic pembahasan melalui penelaahan berbagai literatur yang berhubungan dengan penelitian yang mencakup data primer, sekunder, dantertier. Data-data yang dikumpulkan, dibaca.Hasil penelitian ini yaitu keluarga diharapkan mempunyai kemampuan professional untuk mengantisipasi perilaku keseluruhan anggota keluarga yang terdiri dari berbagai kualitas emosional dan kepribadiannya, serta konseling kelurga dapat mengarahkan dengan melakukan pembiasaan prilaku sehari-hari berdasarkan ajaran agama agar menjadi keluarga yang bertaqwa, posotif produktif dan mandiri melalui relasi individu dan system keluarga yang didasarkan ajaran Islam serta dapat mewujudkan pungsi-pungsi yang ada dalam keluarga, agar keluarga terhindar dari berbagai masalah. Kata kunci: Keluarga Sakinah, Mawaddah, Rahmah dan Hukum Islam